2021
DOI: 10.1039/d1dt00623a
|View full text |Cite
|
Sign up to set email alerts
|

About the importance of purge time in molecular layer deposition of alucone films

Abstract: The deposition rate and properties of MLD films are for a large part determined by what happens during the reactant exposure step. In some cases, however, the purge step is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 52 publications
0
23
1
Order By: Relevance
“…From our previous work, we know that providing longer purge times for DMAI has no significant effect on the overall GPC. 20 In the present work, however, we found that providing longer purge times for EG led to a decrease in the GPC (Fig. 2c).…”
Section: Resultscontrasting
confidence: 58%
“…From our previous work, we know that providing longer purge times for DMAI has no significant effect on the overall GPC. 20 In the present work, however, we found that providing longer purge times for EG led to a decrease in the GPC (Fig. 2c).…”
Section: Resultscontrasting
confidence: 58%
“…Generally, MLD processes are not fully saturated due to non-self-limiting physisorption reactions, creating a so-called "soft" saturation. 28,34,50 The PDIC/ ED and PDIC/HD processes were explored previously with ex situ ellipsometry measurements. 34 For each process the total pulse time of one precursor was maintained constant while the other was varied between 0-60 s (PDIC), 0-3 s (ED), and 0-10 s (HD) for twenty MLD cycles deposited at 60 °C on SiO 2 .…”
Section: Mld Reaction Saturationmentioning
confidence: 99%
“…soft saturation associated with reactant physisorption) consistent with other MLD reactions. 28,34,50 For the experiments below, unless otherwise…”
Section: Mld Reaction Saturationmentioning
confidence: 99%
“…[ 40,46,54,108,109,114,125,148,211–213,218,219,221,226,228,230,234,240,244,245,249,252,255,256,258,260,262,264,267–269,273–277,279–284,325,333–369 ] The bulkier dimethyl aluminum isopropoxide precursor has been successfully used with EG as well. [ 323 ] Different TMA + organic processes have been investigated, e.g., to elucidate the effect of the organic backbone length, i.e., long (1,10‐decanediol) or short (1,6‐hexanediol), on the mechanical properties; indeed, as expected, with the increasing chain length, the stretchability was enhanced.…”
Section: Brief Account Of Ald/mld Processes Developedmentioning
confidence: 98%
“…The prototype process is the one with TMA and EG. [ 111,231,287–332 ] However, TMA works very well with many other organics as well. [ 40,46,54,108,109,114,125,148,211–213,218,219,221,226,228,230,234,240,244,245,249,252,255,256,258,260,262,264,267–269,273–277,279–284,325,333–369 ] The bulkier dimethyl aluminum isopropoxide precursor has been successfully used with EG as well.…”
Section: Brief Account Of Ald/mld Processes Developedmentioning
confidence: 99%